EMS Adherence to a Pre-hospital Cervical Spine Clearance Protocol - Johnson, David; Langdorf, Mark I; Miller, Kenneth; Sebastian, Raynard J (Western Journal of Emergency Medicine, 2001)
Purpose: To determine the degree of adherence to a cervical spine (c-spine) clearance protocol by pre-hospital Emergency Medical Services (EMS) personnel by both self-assessment and receiving hospital assessment, to describe deviations from the protocol, and to determine if the rate of compliance by paramedic self-assessment differed from receiving hospital assessment. Methods: A retrospective sample of pre-hospital (consecutive series) and receiving hospital (convenience sample) assessments of the compliance with and appropriateness of c-spine immobilization. The c-spine clearance protocol was implemented for Orange County EMS just prior to the April-November 1999 data collection period. Results: We collected 396 pre-hospital and 162 receiving hospital data forms. From the pre-hospital data sheet. the percentage deviation from the protocol was 4.096 (16/396). Only one out of 16 cases that did not comply with the protocol was due to over immobilization (0.2%). The remaining 15 cases were under immobilized, according to protocol. Nine of the under immobilized cases (66%) that should have been placed in c-spine precautions met physical assessment criteria in the protocol, while the other five cases met mechanism of injury criteria. The rate of deviations from protocol did not differ over time. The receiving hospital identified 8.0% (13/162; 6/16 over immobilized, 7/16 under immobilized) of patients with deviations from the protocol; none was determined to have actual c-spine injury. Conclusion: The implementation of a pre-hospital c-spine clearance protocol in Orange County was associated with a moderate overall adherence rate (96% from the pre-hospital perspective, and 92% from the hospital perspective, p=.08 for the two evaluation methods). Most patients who deviated from protocol were under immobilized, but no c-spine injuries were missed. The rate of over immobilization was better than previously reported, implying a saving of resources.